2002
DOI: 10.4049/jimmunol.168.4.1664
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Adjustment of Thymic T Cell Production by Clonal Expansion of Premigrant Thymocytes

Abstract: In normal mice, single-positive thymocytes proliferate before being exported into the peripheral T cell pool. We measured the in vivo proliferation rates of mature thymocytes in several TCR transgenic mice. Different monoclonal TCR transgenic single-positive thymocytes proliferated at different rates in a given MHC context. Conversely, mature thymocytes expressing a given TCR, generated in mice of different MHC haplotypes, also showed different rates of proliferation. In p59fyn-deficient mice, the proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…It is also possible that an indeterminant number of SPCD4 and SPCD8 thymocytes may have incorporated BrdU at the DP stage. Previous studies of cell proliferation in the thymus of young adult mice have reported that SPCD4 and SPCD8 thymocytes undergo a late premigrant expansion phase, and that more than 50% of mature SP thymocytes replicate DNA in the 24 h prior to export from the postnatal murine thymus [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that an indeterminant number of SPCD4 and SPCD8 thymocytes may have incorporated BrdU at the DP stage. Previous studies of cell proliferation in the thymus of young adult mice have reported that SPCD4 and SPCD8 thymocytes undergo a late premigrant expansion phase, and that more than 50% of mature SP thymocytes replicate DNA in the 24 h prior to export from the postnatal murine thymus [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, we imposed equal selection fractions (␣ 4 ϭ ␣ 8 ) and equal export fractions ( f 4 ϭ f 8 ). We still found the best fit for our original model, where the CD4:CD8 ratios in the thymus and spleen are set, respectively, by the difference in thymic selection coefficient (␣ 4 and ␣ 8 ), and in fraction exported CD4 and CD8 thymocytes migrating to the spleen ( f 4 and f 8 ). This means that five times more CD4 than CD8 thymocytes are generated from DP cells (␣ 4 /␣ 8 ϭ 5).…”
Section: Selection In the Thymus And Export Rate To Peripherymentioning
confidence: 99%
“…It has been shown by Campion et al (29) that premigrant thymocytes proliferate in a TCR-dependent manner before leaving the thymus. The loss of Egr1 could lead to decreased numbers of thymocytes emigrating the thymus because of reduced proliferation before exiting the thymus.…”
Section: Egr1mentioning
confidence: 99%